2008
DOI: 10.1002/j.0022-0337.2008.72.8.tb04570.x
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic Orthodontic Treatment Using the Invisalign Appliance for Moderate to Complex Malocclusions

Abstract: In this report, three patients were treated with a new treatment protocol for Invisalign to demonstrate that a variety of complex malocclusions can be successfully treated using this protocol, including correction of moderate crowding, correction of moderate Class II division 1, and deep overbite. Previous studies of Invisalign showed significant limitations for more complex orthodontic treatment, although a few recent case reports have shown successfully completed moderate to difficult orthodontic malocclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 21 publications
2
76
0
7
Order By: Relevance
“…It has been reported that the expansion extent with Invisalign should be 2-4 mm. 17 Ali et al 7 indicated that the range of dental expansion should be limited to 2-3 mm in each quadrant to reduce the risk of gingival recession. In the current study, the prescribed amount of expansion for each participant was customized based on measurements of the dentition and CBCT to be within a safe range.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the expansion extent with Invisalign should be 2-4 mm. 17 Ali et al 7 indicated that the range of dental expansion should be limited to 2-3 mm in each quadrant to reduce the risk of gingival recession. In the current study, the prescribed amount of expansion for each participant was customized based on measurements of the dentition and CBCT to be within a safe range.…”
Section: Discussionmentioning
confidence: 99%
“…The system of forces and moments to correct malocclusions is generated by the difference between the appliance shape and the dentition geometries. A single template is able to perform only a small part (from 0.15 to 0.25 mm for translations and no more than 2 degrees for rotations) [1,3] of the complete tooth movement. Therefore, a full treatment consists of a set of templates with varying shapes from the initial anatomical geometry to the target tooth positions.…”
Section: Introductionmentioning
confidence: 99%
“…Even if RTA-based orthodontic treatments are becoming an effective solution for moderate to complex malocclusions [3], most of the technical literature is focused on case reports and system descriptions. There have been few evidence-based attempts to describe the RTA behaviour in delivering forces able to produce specific tooth movements.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most relevant problems, particularly with regard to adult patients, is represented by the need to undergo orthodontic therapy for several months. The aesthetic problem, associated to the worsening of oral hygiene conditions, may discourage many patients even before the beginning [ 2 ]. Invisalign system (Align Technology, Inc., San Josè, California, USA) could represent a suitable solution to solve such problematic [ 3 – 5 ].…”
Section: Introductionmentioning
confidence: 99%